The Relationship between Chemotherapy and Level of IL-10 in Patients with Breast Cancer - Hamid Naji Obied (Journal of Global Pharma Technology, 2018)
Background: Cancer is a group of diseases that cause cells in the body to change and grow out of control and most types of cancer cells eventually form a lump or mass called a tumor. Aim of this study; A descriptive study was conducting to determine the level of IL-10 and the lymphocytes as well as monocytes count in women with breast cancer, and to investigate the effect of chemotherapy on these two parameters. Methods: A non-probability (purposive sample) of (30) patients diagnosed previously with breast cancer were selected before (pre-chemotherapy) and after taking the first dose of chemotherapy, and 30 samples of healthy females as control group. Blood sampling were collecting and tested to estimate the level of IL-10(ELISA) and CBC to numerate the lymphocyte and monocyte.  The results of this study indicated that there was a significant increase in the level of IL-10in pre-chemotherapy patients group compared with control group, also there was elevated in lymphocytes count pre-chemotherapy group in comparisons with control group. Conclusion: In this study can conclude the amount of IL-10 and lymphocyte count in the women with breast cancer before chemotherapy were increased level than after chemotherapy.Keywords: Breast cancer, Chemotherapy, Lymphocyte, IL-10.